Positive Effects of NPY1 Receptor Activation on Islet Structure Are Driven by Pancreatic Alpha- and Beta-Cell Transdifferentiation in Diabetic Mice - Lafferty, Ryan A.; Tanday, Neil; Moffett, R. Charlotte; Reimann, Frank; Gribble, Fiona M.; Flatt, Peter R.; Irwin, Nigel (Frontiers in Endocrinology, 2021)
Enzymatically stable and specific neuropeptide Y1 receptor (NPYR1) agonists, such as sea lamprey PYY(1-36) (SL-PYY(1-36)), are believed to improve glucose regulation in diabetes by targeting pancreatic islets. In this study, streptozotocin (STZ) diabetic transgenic GluCreERT2;ROSA26-eYFP and Ins1Cre/+;Rosa26-eYFP mouse models have been used to study effects of sustained NPYR1 activation on islet cell composition and alpha- and beta-cell lineage transitioning. STZ induced a particularly severe form of diabetes in Ins1Cre/+;Rosa26-eYFP mice, but twice-daily administration (25 nmol/kg) of SL-PYY(1-36) for 11 days consistently improved metabolic status. Blood glucose was decreased (p < 0.05 - p < 0.001) and both fasted plasma and pancreatic insulin significantly increased by SL-PYY(1-36). In both GluCreERT2;ROSA26-eYFP and Ins1Cre/+;Rosa26-eYFP mice, STZ provoked characteristic losses (p < 0.05 - p < 0.001) of islet numbers, beta-cell and pancreatic islet areas together with increases in area and central islet location of alpha-cells. With exception of alpha-cell area, these morphological changes were fully, or partially, returned to non-diabetic control levels by SL-PYY(1-36). Interestingly, STZ apparently triggered decreased (p < 0.001) alpha- to beta-cell transition in GluCreERT2;ROSA26-eYFP mice, together with increased loss of beta-cell identity in Ins1Cre/+;Rosa26-eYFP mice, but both effects were significantly (p < 0.001) reversed by SL-PYY(1-36). SL-PYY(1-36) also apparently reduced (P <0.05) beta- to alpha-cell conversion in Ins1Cre/+;Rosa26-eYFP mice and glucagon expressing alpha-cells in GluCreERT2;ROSA26-eYFP mice. These data indicate that islet benefits of prolonged NPY1R activation, and especially restoration of beta-cell mass, are observed irrespective of diabetes status, being linked to cell lineage alterations including transdifferentiation of alpha- to beta-cells.